PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN BAMBOOZLE UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Cahya Putriani; Rusdial Marta; Iis Aprinawati; Fadhilaturrahmi; Sumianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the problem that when students are given a problem, they are unable to provide opinions to solve the problem. When asked questions, students tend to remain silent and are unable to answer the questions. The study aims to describe the planning, implementation, and improvement of the application of the Bamboozle-assisted Problem-Based Learning (PBL) model to improve the mathematical critical thinking skills of fifth-grade elementary school students. This study is a classroom action research (CAR) conducted at UPT SDN 009 Bangkinang Kota with 15 fifth-grade students as the research subjects. The research was conducted in two cycles, with each cycle consisting of two meetings. Each cycle included the stages of planning, implementation, observation, and reflection. Data collection techniques used tests, observation, and documentation. The results showed that the students' mathematical critical thinking skills improved from the pre-action phase with a classical mastery level of 23%, increasing in cycle I meeting 1 to 20%, cycle I meeting 2 to 23%, cycle II meeting 1 to 48%, and cycle II meeting 2 to 56% with an average score of 84.2 (critical category). In conclusion, the application of the Bamboozle-assisted PBL model can improve the mathematical critical thinking skills of fifth-grade students at SDN 009 Bangkinang Kota.